Agglomeration in preventing success for CNTs continuous production in a fluidized – bed CVD - Lim, Siang Yi Ng (2011)
At the first stage in this research, Fe(NO3)3.9H2O and Al2O3 was used to formed Fe(NO3)3 catalyst using wet impregnation method. Carbon nanotubes (CNTs) was then grown using the prepared catalyst introduced into fluidized-bed reactor. CNTs grown in the fluidized-bed was later purified in acid follow by thermal oxidation. After purification process, carbon nanotubes (CNTs) were characterized using scanning electron microscope (SEM), transmission electron microscopy (TEM) and Raman spectroscopy. In this experiments, large quantity of agglomerates as much as 7 g is synthesized in a different way than other authors. This agglomerates consists of different size of CNTs and some amorphous carbon. The causes for the failure of continuous CNTs synthesizing is determined through the analysis of agglomerate formation. A new unit (g/mole) is used to measuring CNTs yields to provide a bigger picture than the commonly used percentage yields.